2006
DOI: 10.1029/2005jb003831
|View full text |Cite
|
Sign up to set email alerts
|

Local time stacking of geomagnetic solar daily variations

Abstract: [1] Regular geomagnetic solar daily variations, the Sq signal, is used in electromagnetic induction studies to investigate the electrical conductivity structure of Earth's upper mantle. Traditionally, Sq induction studies employ observatory magnetic data from a few quiet days in which the overprint on the regular Sq ionospheric current vortices from various irregular disturbances is minimal. Active days are typically discarded, a procedure which results in a gappy time series that is difficult to analyze. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Le Mouë l et al, 2005) showed that long-term trends are similar for different choices of the days. This fact has been especially investigated by Everett (2006), who concluded that the average local time variation on active days resembles typical quiet day variations except for a multiplicative scale factor. The monthly mean range was therefore computed for each observatory as the average of the amplitude of the daily diurnal variation for the corresponding five quietest days.…”
Section: Results Of Analysismentioning
confidence: 93%
“…Le Mouë l et al, 2005) showed that long-term trends are similar for different choices of the days. This fact has been especially investigated by Everett (2006), who concluded that the average local time variation on active days resembles typical quiet day variations except for a multiplicative scale factor. The monthly mean range was therefore computed for each observatory as the average of the amplitude of the daily diurnal variation for the corresponding five quietest days.…”
Section: Results Of Analysismentioning
confidence: 93%
“…Periods separate from the tidal and Sq periods are usually employed for the estimation to avoid not only the effects of the line spectra but also the side lobes of the line spectra that might exist due to seasonal variations of the Sq field (e.g. Schmucker 1999; Everett 2006).…”
Section: Features Of Observed Responsesmentioning
confidence: 99%
“…Periods separate from the tidal and Sq periods are usually employed for the estimation to avoid not only the effects of the line spectra but also the side lobes of the line spectra that might exist due to seasonal variations of the Sq field (e.g. Schmucker 1999;Everett 2006). Although the periods used to estimate the response functions were carefully chosen to be separate from the Sq and tidal periods, the estimated response functions show a characteristic feature if the periods are in the ME band, as it is presented in the next section.…”
Section: Section Averaged Spectra After Detidingmentioning
confidence: 99%
“…The selection of suitable days follows the quietness definition introduced by Schmucker (1999). We understand that this definition involves several problems (Everett 2006) which however are not very serious in the present case of answering Rikitake's question. It is based on a fixed upper limit for a specified sum of 3‐hr ap indices.…”
Section: Comparison Of Observations With Predictionsmentioning
confidence: 99%